9x + 16 = 6x + 1
Subtract 6x from both sides:
3x + 16 = 1
Subtract 16 from both sides:
3x = -15
Divide by 3:
x = -5
So x = -5.
solve for x.
9x + 16 = 6x + 1
9 answers
4x - 3 = 3x - 9
4x - 3 = 3x - 9
Subtract 3x from both sides:
x - 3 = -9
Add 3 to both sides:
x = -6
So x = -6.
Subtract 3x from both sides:
x - 3 = -9
Add 3 to both sides:
x = -6
So x = -6.
3x - 3 = 6x + 18
3x - 3 = 6x + 18
Subtract 3x from both sides:
-3 = 3x + 18
Subtract 18 from both sides:
-21= 3x
Divide by 3:
x= -7
So, x = -7.
Subtract 3x from both sides:
-3 = 3x + 18
Subtract 18 from both sides:
-21= 3x
Divide by 3:
x= -7
So, x = -7.
4x + 8 = 3x - 10
To solve for x in the equation 4x + 8 = 3x - 10:
First, let's subtract 3x from both sides to get all the x terms on one side:
4x - 3x + 8 = 3x - 3x - 10
This simplifies to:
x + 8 = -10
Subtract 8 from both sides:
x = -10 - 8
x = -18
Therefore, the solution to the equation is x = -18.
First, let's subtract 3x from both sides to get all the x terms on one side:
4x - 3x + 8 = 3x - 3x - 10
This simplifies to:
x + 8 = -10
Subtract 8 from both sides:
x = -10 - 8
x = -18
Therefore, the solution to the equation is x = -18.
13x + 26 = 3x - 34
To solve for x in the equation 13x + 26 = 3x - 34:
First, subtract 3x from both sides to get all the x terms on one side:
13x - 3x + 26 = 3x - 3x - 34
This simplifies to:
10x + 26 = -34
Subtract 26 from both sides:
10x = -60
Divide by 10:
x = -60/10
x = -6
Therefore, the solution to the equation is x = -6.
First, subtract 3x from both sides to get all the x terms on one side:
13x - 3x + 26 = 3x - 3x - 34
This simplifies to:
10x + 26 = -34
Subtract 26 from both sides:
10x = -60
Divide by 10:
x = -60/10
x = -6
Therefore, the solution to the equation is x = -6.